2013
DOI: 10.3389/fmicb.2013.00152
|View full text |Cite
|
Sign up to set email alerts
|

Growth and membrane fluidity of food-borne pathogen Listeria monocytogenes in the presence of weak acid preservatives and hydrochloric acid

Abstract: This study addresses a major issue in microbial food safety, the elucidation of correlations between acid stress and changes in membrane fluidity of the pathogen Listeria monocytogenes. In order to assess the possible role that membrane fluidity changes play in L. monocytogenes tolerance to antimicrobial acids (acetic, lactic, hydrochloric acid at low pH or benzoic acid at neutral pH), the growth of the bacterium and the gel-to-liquid crystalline transition temperature point (Tm) of cellular lipids of each ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 37 publications
(45 reference statements)
0
7
0
1
Order By: Relevance
“…Thermophiles, as extremophiles, are a good source of thermostable enzymes and have been exploited for pharmaceutical and many other industrial applications (Lin et al 2013;Oliveira et al 2013;Panda et al 2013;Park et al 2013). It is known that microbial adaptation is regulated by changes in cellular enzymes, membrane lipids, and their morphology, leading to a variation in functional dynamics and plasticity through redox and signaling systems of the organism (Contera et al 2010;Pocock et al 2011;Diakogiannis et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thermophiles, as extremophiles, are a good source of thermostable enzymes and have been exploited for pharmaceutical and many other industrial applications (Lin et al 2013;Oliveira et al 2013;Panda et al 2013;Park et al 2013). It is known that microbial adaptation is regulated by changes in cellular enzymes, membrane lipids, and their morphology, leading to a variation in functional dynamics and plasticity through redox and signaling systems of the organism (Contera et al 2010;Pocock et al 2011;Diakogiannis et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Levels of long-chain fatty acids, UFAs, and ergosterol were restored or increased upon CgMED3AB overexpression, which might contribute to improve the membrane fluidity and integrity at pH 2.0. Note that squalene accumulated in the Cgmed3ABΔ strain at pH 2.0, inhibiting ergosterol synthesis and resulting in increased membrane permeability and significantly defective growth at low pH (48,49). Previous reports found that ergosterol was essential for maintaining membrane integrity and rigidity, both of which play a vital role against acid stress (42,50,51).…”
Section: Discussionmentioning
confidence: 93%
“…Cells adapt to the changes in environment through modulation of membrane properties and lipid composition resulting in altered membrane fluidity (Barrera et al, 2012 ). Cell membrane serves as a barrier for entry or exit of biomolecules across the cells and intrinsic (inherent) or acquired cellular changes due to alteration in structure may accompany the cells to modulate the pathogenicity and virulence of the organism (Diakogiannis et al, 2013 ). In order to determine the effects of endogenous sterol derivatives on membrane fluidity, the biophysical properties of the B. anthracis membrane was accessed in presence of ZA using fluorescence polarization and TRFS.…”
Section: Resultsmentioning
confidence: 99%